Crude oil biodegradation by bacterial cells immobilized on corn starch-alginate beads (Research, Society and Development, 2021)
Immobilized cells have shown advantages in removing hydrocarbons from oil compared to the use of free cells. This work aimed to evaluate the potential of hydrocarbon degradation by bacteria immobilized in support matrices composed of commercial potassium alginate and corn starch. The polymeric immobilizing matrix was developed using dental alginate 2% and corn starch 0.5% and 1%. The matrices have macropores internally, good ability to immobilize cells, increasing baseline respiration (F2 and F3: 4 mg / l CO2 60 days), bacterial biomass (F1: 1.5 x 106 CFU / g 60 days) and the removal of n- alkanes and PAHs of the sediment, when compared to free cells (0 mg / l CO2; 0.3 x 106 CFU / g 60 days). The aromatics hydrocarbons benzo (a) anthracene and anthracene were not degraded. Naphthalene and dibenzo (a) anthracene reached degradation rates of 60% and 80%, respectively. Therefore, the consortium tested and the polymer matrix developed are promising for use in bioremediation of environments contaminated by hydrocarbons.